Terapi Forgiveness pada Anime Wonder Egg Priority dalam Perspektif Bimbingan dan Konseling Islam - Devi Kirani; Lilik Sriyanti (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The development of Islamic guidance and counseling services requires innovation, one of which is through the use of film media. Films are able to present the dynamics of emotions and psychological conflicts that are relevant to the lives of counselees. The Wonder Egg Priority anime presents issues of trauma, inner wounds, and self-acceptance that are closely related to the forgiveness therapy process. Therefore, this study aims to analyze the Wonder Egg Priority anime and its integration with the perspective of Islamic guidance and counseling to produce innovative services. This type of research is descriptive qualitative research. Researchers use data analysis techniques in the form of multimodal discourse analysis on films, allowing researchers to explore the deep meaning of the elements contained in the video or film. The results of the study show that: (1) The characters in the anime have complex conflicts, as conflicts that often occur among teenagers such as past trauma, conflicts with family, and unresolved inner wounds (2) The Wonder Egg Priority anime contains aspects of forgiveness therapy (forgiving oneself, forgiving others, and forgiving situations/circumstances) and stages of forgiveness therapy (self- disclosure, decision stage, action-taking stage, and deepening stage); (3) The Wonder Egg Priority anime is in line with forgiveness therapy from the perspective of Islamic guidance and counseling because it emphasizes cleansing the heart, patience, and compassion.